Performance Enhancement of High Speed Interior Permanent Magnet Synchronous Motors Using Superior Magnetic Material (2023)
This paper presents the application of higher-grade magnetic material for performance improvement of interior permanent magnet synchronous motors (IPMSM) for high-speed applications. The efficiency and weight of the motor are important performance parameters for high-speed applications. Efficiency improvement with simultaneous weight reduction is the key design issue for many specific applications. The main contribution of this work is to explore the possibility of using high-grade magnetic material for efficiency improvement with a simultaneous weight reduction of IPMSM motors. Three different standard rating motors were designed with the usual M19 material, and their performance was estimated. Finite element modelling and simulation was carried out to validate the initial design. For performance comparison, initial designs were regarded as reference designs. Design improvement was carried out with the application of high-grade magnetic material Hiperco 50A and its influence on the performance of IPMSM motors was analyzed. Three different standard ratings motors were considered in this work to analyze the effect of material in a wide range. Improved design was also validated with finite element modelling and simulation. It was observed that the efficiency is effectively improved with weight reduction using Hiperco 50A material in all three standard-rating IPMSM motors.